If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -1(3x + -7) = 0 Reorder the terms: 5x + -1(-7 + 3x) = 0 5x + (-7 * -1 + 3x * -1) = 0 5x + (7 + -3x) = 0 Reorder the terms: 7 + 5x + -3x = 0 Combine like terms: 5x + -3x = 2x 7 + 2x = 0 Solving 7 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 2x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 2x = 0 + -7 2x = 0 + -7 Combine like terms: 0 + -7 = -7 2x = -7 Divide each side by '2'. x = -3.5 Simplifying x = -3.5
| 8c^2+22cd+9d^2=0 | | 105x^4+60x^3-30x^6= | | 6*x^4-2*x^2=n | | -13a+6-9a+12a= | | 6c^2+7cd-5d^2=0 | | (75)(5x-2)= | | 2a^2-11ab-6b^2=0 | | 3a^2+ab-10b^2=0 | | 6x^2*x^2=n | | 6+2(7+x)+8y=36+2y+10x | | 3x-1+2x^2=n | | 6x(-2x+1)=-11(x+1) | | F(-3)=x^4+3x^2+5 | | (11b-4)-5(2b+2)=-4 | | 6+2(7+x)=36+2y+10x | | 3=7y-5y-3 | | 4x+5y=-13 | | 14=-15x+4x | | 8x+6x+4+9=5x+5+8x | | 14=15x+4x | | 8=6y-4y | | 5x+11x=64 | | 3-x-7=3(x+1) | | n+5-5=12-5 | | 3-(5)-7=3((-5)+1) | | 3x^2-7+2=0 | | x+4(x-6)= | | 2(3x+2)=26 | | 4(-4)+8(-2)+3(-2)+6= | | -3.5x^2+40x+0=0 | | (-12-3)(-12-2)=(-12+5)(2*-12-3)+21 | | 7p+9=17+6p |